Bahraini Teachers’ Perceptions on the Challenges of Remote Teaching for Autistic Children - Daghustani, Wid Hussain; MacKenzie, Alison (Research in Social Sciences and Technology- OpenED Network, 2024)
This research aims to understand how teachers of autistic children responded to teaching remotely during the COVID-19 pandemic. Six teachers who work in an autism centre took part in face-to-face semi-structured interviews in the Kingdom of Bahrain on their perspectives of teaching autistic children remotely and how their mothers adapted to this mode of teaching. The teachers reported that the unprecedented change was challenging for autistic children and their families, but especially for mothers, who were in all cases, the primary caretakers. The effectiveness of remote teaching depended on the cooperation and the willingness of the mother and child to engage in the process. Overall, teachers agreed that in comparison to face-to-face teaching, remote teaching was not a positive experience.